Implementasi Aplikasi Zahir dalam Meningkatkan Transparansi Pengelolaan Keuangan yang Amanah di Yayasan Kasih Anak Kanker Indonesia Bandung - Gamat, Mutia Taqina; Nadeak, Putry H.; Ramadhani, Annas Rahmat; Nuzul, Dinda Amanda Ainun; Nugraha, Muhamad Arif; Nurasman, Muhammad Syaiful; Qolbi, Satria Kharimul (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
Nonprofit organizations are required to maintain financial transparency and accountability in order to sustain public trust, particularly in managing donation funds. This study examines the implementation of Zahir Accounting in enhancing transparency and trustworthy financial management at the Indonesian Cancer Children’s Foundation (YKAKI) Bandung Branch. The objective of this research is to analyze the role of the application in improving reporting efficiency, orderly record-keeping, and accountability, especially among staff who do not entirely have accounting backgrounds. The study employs a qualitative field approach through observation, in-depth interviews, and documentation, with data validation conducted using triangulation. The findings indicate that Zahir Accounting improves documentation structure, reporting timeliness, and transaction traceability, thereby strengthening managerial oversight and accountability to donors. However, the effectiveness of the system remains dependent on user discipline and strengthened internal control. These findings affirm that accounting digitalization supports administrative transparency as well as the value of amanah in nonprofit financial governance